Association of immunoglobulins and complement levels with pemphigus in patients at the Khartoum Dermatology and Venereal Disease Hospital, Sudan - Omer Osman Elhag; Mohammed S. Abduhameed; Ismaeel O. Khalid; AbdulAzeem Hijawi; Mohamed O. Andarawi; Saadalnour A. Mustafa; Adil A. Yousif; Shawgi A Elsiddig; Asaad Babker (Italian Journal of Medicine, 2024)
Pemphigus is a group of autoimmune intra-epidermal blistering diseases that affect both the skin and mucous membranes. Characteristic histological features of pemphigus include intra-epidermal blisters and acantholysis, which is the loss of connections between epidermal cells. A cross-sectional hospital-based study was conducted in the period between January 2016 and January 2019. A total of 549 cases were selected; 92 cases were clinically diagnosed as pemphigus, and direct immunofluorescence (DIF) was applied for immunoglobulin (Ig) A, IgG, IgM, and C3 to confirm clinical diagnosis. Bullous pemphigoid (BP) was the most common autoimmune skin condition, comprising 29.3% of cases, predominantly affecting females (19.6%). Pemphigus vulgaris (PV) followed with 32.6% of cases, evenly distributed between males and females. Lichen planus pemphigoid accounted for 17.4%, with a higher prevalence in females (13.0%). Other conditions, such as pemphigus gestationis and bullous lupus erythematosus, were rare, each affecting only one gender. Epidermolysis bullosa acquisita was seen only in males, while linear IgA bullous dermatosis was slightly more common in females. Pemphigus foliaceus (PF) and pemphigus vegetans were infrequent, with the first one more common in males and the second one more common in females. Paraneoplastic pemphigus (PNP) and IgA pemphigus had the lowest incidence, with PNP affecting one male and IgA pemphigus equally distributed between genders. The study found PV (32.6%) to be the most common autoimmune blistering disease, followed by BP (29.3%), with females more frequently affected. DIF was effective in confirming clinical diagnoses across various subtypes.